1235. Roles of Tetracyclines for Treatment of Stenotrophomonas maltophilia Pneumonia. (4th December 2021) - Alhayani, Taha; Philpott, Carolyn; Liao, Siyun; Gentene, Anthony; Mueller, Eric
Abstract: Background: Stenotrophomonas maltophilia is a multidrug resistant organism with limited antibiotic treatment options. Sulfamethoxazole-trimethoprim (TMP-SMZ) is considered first line agent based on in vitro studies and clinical evidence. Minocycline has been showed to be active on in vitro studies and also has been explored in small retrospective studies However, doxycycline in the same class has variable in susceptibility in in vitro studies and has not been evaluated for efficacy in treatment of S. maltophilia infections The purpose of this research is to compare minocycline and doxycycline to TMP-SMZ for treatment of S. maltophilia pneumonia. Methods: This retrospective, multi-center study evaluated hospitalized patients treated for S. maltophilia pneumonia with minocycline, doxycycline, or TMP-SMZ for clinical success, microbiologic success, and recurrence or reinfection within 30 days that required treatment. The inclusion criteria were patients ≥18 years old with S. maltophilia confirmed on respiratory culture from January 2013 to November 2020. Patients were classified as treatment with tetracyclines (minocycline or doxycycline) or TMP-SMZ based on definitive agent used for ≥50% of the treatment course and a minimum of four days. Patients with S. maltophilia resistant or intermediate to definitive therapy, and patients with combination therapy for treatment for S. maltophilia pneumonia were excluded. Results: A total of 21 patients were included in tetracyclines group and 59 patients included in TMP-SMZ group. There was no difference in clinical success (28.6% vs. 25.4%; P = 0.994) or microbiologic success (n=28, 55.6% vs. 66.4%; P = 0.677) between tetracyclines and TMP-SMZ, respectively. Recurrence or reinfection requiring treatment (n=24) was higher in the tetracyclines group but not statistically significant compared to TMP-SMZ (66.7% vs. 26.7%; P = 0.092). A subgroup analysis showed no difference between doxycycline, minocycline, and TMP-SMZ for these three aims. Conclusion: Clinical and microbiologic success were similar in patients treated with tetracyclines compared to TMP-SMZ for S. maltophilia pneumonia. This data suggests minocycline and doxycycline may be an option to treat S. maltophilia pneumonia, but conclusive clinical data continues to be lacking. Disclosures: Anthony Gentene, PharmD, advisory board with Theravance Biopharma and Mylan (Consultant)